2016
DOI: 10.1007/s00464-016-5257-3
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic common bile duct exploration: a safe and definitive treatment for elderly patients

Abstract: Although elderly patients are frequently confronted with coexisting disorders, LCBDE can be considered as a safe and effective technique in choledocholithiasis treatment for elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 27 publications
5
10
0
Order By: Relevance
“…In the mid-1990s, Traverso [14], who had done some early LCBDE studies, recommended one-step LCBDE to treat CBD stones, even though he supported the transcystic approach. Similar to Traverso and other scholars' view [4,6,15], we consider that ERCP may lead to disruption of sphincter Of Oddi and induce several postoperative complications such as pancreatitis, bleeding, and perforation.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In the mid-1990s, Traverso [14], who had done some early LCBDE studies, recommended one-step LCBDE to treat CBD stones, even though he supported the transcystic approach. Similar to Traverso and other scholars' view [4,6,15], we consider that ERCP may lead to disruption of sphincter Of Oddi and induce several postoperative complications such as pancreatitis, bleeding, and perforation.…”
Section: Discussionsupporting
confidence: 67%
“…The WBC count and ALB and TBIL levels were significantly improved regardless of the patients' preoperative criticality and ASA score, and changes in most evaluated parameters were statistically significant. The study results of Liu [5] and Zheng [6], which compared between older than 70 patients and younger than 70 patients, also mentioned that LCBDE was effective for elderly people with CBD stones. Moreover, Zhu [15] reported that LCBDE with T-tube could improve liver function effectively and rapidly.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…(28,29). Furthermore, LCBDE is an effective technique for choledocholithiasis with a proven safety and excellent outcome for elderly patients (30). The common bile duct exploration can be achieved via a transcystic (TC) or transductal (TD) approach.…”
Section: Discussionmentioning
confidence: 99%
“…[5] However, some recent studies proved laparoscopic CBD exploration to be successful in older and cirrhotic patients. [22][23][24] Among our patients, serious secondary conditions were observed in 28.3% cases, including pregnancy in four patients, cirrhosis in four patients and older age in seven patients, and no complication was identified regarding such conditions. Impacted stones comprise the main reasons of failures both in laparoscopic and endoscopic managements.…”
Section: Discussionmentioning
confidence: 68%